Organometallic Hexahapto Functionalization of Single Layer Graphene as a Route to High Mobility Graphene Devices. (8th November 2012) - Sarkar, Santanu; Zhang, Hang; Huang, Jhao‐Wun; Wang, Fenglin; Bekyarova, Elena; Lau, Chun Ning; Haddon, Robert C.
<x xml:space="preserve">Abstract</x> Organometallic hexahapto (η6)‐chromium metal complexation of single‐layer graphene, which involves constructive rehybridization of the graphene π‐system with the vacant chromium dπ orbital, leads to field effect devices which retain a high degree of the mobility with enhanced on‐off ratio. This η6 mode of bonding is quite distinct from the modification in electronic structure induced by conventional covalent σ‐bond formation with creation of sp3 carbon centers in graphene lattice and this chemistry is reversible. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>